RONC-22. SECOND TUMORS IN PEDIATRIC PATIENTS TREATED WITH PROTON THERAPY TO THE CENTRAL NERVOUS SYSTEM - Indelicato, Daniel J (Neuro Oncol, 2020)
BACKGROUND: Previous institutional data suggests the 10-year cumulative incidence of second tumors is 3% in children treated with photon radiation for central nervous system (CNS) malignancy, with 90% of these tumors occurring in areas receiving ≤36 Gy. Comparative figures for children treated with proton therapy (PT) does not exist. METHODS: 1056 consecutive pediatric patients with a median follow-up of 5.0 years were treated between 2006–2019 with double-scattered PT to a site within the craniospinal axis. 230 patients were ≤3 years old and 14 had neurofibromatosis. A second tumor was defined as any solid neoplasm with histologic features different from the original tumor that had arisen within the irradiated volume. RESULTS: Five patients developed second tumors resulting in a 5- and 10-year cumulative incidence of 0.2% (95% CI: 0–1.2%) and 1.6% (95% CI: 0.6%-3.9%), respectively. Of those who developed second tumors, median age at radiation was 4.3 years old (range, 2.1 to 5.1 years old) and diagnoses consisted of medulloblastoma (n=2), ependymoma (n=2), and craniopharyngioma (n=1). The second tumors included high grade gliomas (n=3) and high grade sarcoma (n=1) that occurred in regions receiving at least 54 Gy. One patient with neurofibromatosis developed both a low-grade glioma and choroidal melanoma in craniospinal irradiation regions receiving 36 Gy. Four of five patients with second tumors are alive. CONCLUSION: The reduction in moderate-to-low dose radiation exposure from proton therapy may be associated with a decreased incidence of second tumors in children treated for CNS neoplasms. More follow-up is needed to confirm these findings.